2019
DOI: 10.3390/polym11111791
|View full text |Cite
|
Sign up to set email alerts
|

Water Footprint Assessment of Selected Polymers, Polymer Blends, Composites, and Biocomposites for Industrial Application

Abstract: This paper presents a water footprint assessment of polymers, polymer blends, composites, and biocomposites based on a standardized EUR-pallet case study. The water footprint analysis is based on life cycle assessment (LCA). The study investigates six variants of EUR-pallet production depending on the materials used. The system boundary included the production of each material and the injection molding to obtain a standardized EUR-pallet of complex properties. This paper shows the results of a water footprint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 45 publications
(48 reference statements)
0
19
0
1
Order By: Relevance
“…All these features contribute to the product's final properties and the choice of the manufacturing technique. In recent years, even if the price criteria are still crucial at the stage of project and manufacturing on the large-scale, more attention has been paid to the sustainability of individual components that make up the final carbon and water footprint of a product [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…All these features contribute to the product's final properties and the choice of the manufacturing technique. In recent years, even if the price criteria are still crucial at the stage of project and manufacturing on the large-scale, more attention has been paid to the sustainability of individual components that make up the final carbon and water footprint of a product [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…They stand for 86%, 94%, and 99.6%, respectively, of carbon, ecological, and water footprints. Such a high share of irrigation in the total value of the water footprint of cotton fibers was discussed in our previous work and the works of other research groups [49,58,59].…”
Section: Carbonmentioning
confidence: 67%
“…For the presented work, data were collected from scientific publications as well as reports and databases including Ecoinvent database v 3.1. This information was also provided in our previous work [49]. The data available in the Ecoinvent database are developed based on technological data obtained from companies, industrial associations, and research institutes operating on the market.…”
Section: Input Datamentioning
confidence: 99%
“…The amount of void in the RH-rHDPE foam was represented as void fraction (V f ) and cell density (N f ), which is the number of cells per unit volume, and calculated using Equations (1) and (2). The average cell size (d) was calculated using Equation (3) [29,34].…”
Section: Cell Size Density and Morphology Of The Hr/rhdpe Composite mentioning
confidence: 99%
“…Fabricating high-performance polymer matrix composites has been explored tremendously, and the current inventions are moving towards green technology, which has minimum emission of toxic materials and is environmentally friendly. Pertaining to this situation, numerous studies have reported on the production of natural fibre-reinforced polymer composite, particularly in polymer matrix composites [1,2]. Polymer matrix composites form the preferred group of advanced materials in structural applications, such as in aerospace, construction or automotive parts, due to their high specificity.…”
Section: Introductionmentioning
confidence: 99%